Iterative Development of an mHealth Intervention to Support Antiretroviral Therapy Initiation and Adherence Among Female Sex Workers in Mombasa, Kenya. (March 2020) - Aunon, Frances M.; Okada, Elena; Wanje, George; Masese, Linnet; Odeny, Thomas A.; Kinuthia, John; Mandaliya, Kishorchandra; Jaoko, Walter; Simoni, Jane M.; McClelland, R. Scott
Abstract: Nurses have an integral role to play in achieving the 95-95-95 goals to stem the HIV epidemic. We used the Information–Motivation–Behavioral Skills (IMB) theoretical model to develop a nurse-delivered, mHealth intervention to support antiretroviral therapy adherence among female sex workers living with HIV in Mombasa, Kenya. Twenty-three purposively sampled female sex workers living with HIV participated in 5 focus group discussions to iteratively develop the message content as well as the format and structure of the nurse-delivered, text-based intervention. Focus group discussion interview guides were developed in accordance with the IMB model. Transcripts were analyzed according to IMB themes, and findings were used to develop the intervention. Information-oriented texts addressed concerns and misconceptions; motivation-oriented texts reinforced women's desires to feel healthy enough to engage in activities; and behavioral skills-oriented texts included strategies to remember medication doses. The nurse-delivered, theory-based, culturally tailored intervention to support medication adherence was evaluated.